OUTCOME OF DYNAMIC COMPRESSION PLATE WITH DORSAL RADIAL SLIDING GRAFT TECHNIQUE FOR WRIST ARTHRODESIS IN BRACHIAL PLEXUS INJURY PATIENTS - Jan, Asad Ullah; Cheema, Tehseen Ahmed; Ahmad, Sajjad; Shafiq, Muhammad; Hussain, Baqir; Ullah, Farman (Journal of Ayub Medical College Abbottabad, 2019)
Background: The incidence of brachial plexus injuries have shown to increase over the years. It is 1-2% worldwide according to the WHO. In global brachial plexus injuries and lower root injures when the wrist and hand functions are lost, wrist arthrodesis is a viable option. In other cases, when there are some residual hand functions, wrist arthrodesis stabilizes the wrist as well as provides donor muscles tendons to enhance finger functions. Apart from these, wrist arthrodesis increase grip strength and power, and also wrist in extension assume a better shape cosmetically. Purpose: Outcome of dynamic compression plate with dorsal radial sliding graft for wrist arthrodesis in terms of time to union and complications in brachial plexus injury patients. Methods: This is a retrospective chart review of patients treated in National Orthopaedic Hospital Bahawalpur, from January 2011 to Sep 2017. All the patients with brachial plexopathies of both genders from age 14 to 60 were included in the study. Data was analysed using MS Excel 2010. Results: A total of 34 patients were included in the study. Road traffic accidents was the major cause of the injury having 30 (88%) patients whereas birth palsy and gunshots had 2 patients each (6%). Twenty-three patients had no associated fracture while remaining 11 patients had a fracture. There was union in all patients (100 %) and mean time to union was 6.5 weeks (range 6-8) radiologically. Mean follow up was 20.2 months (range 1.5-72). Keywords: Brachial plexus injury; wrist arthrodesis; radius sliding graft; dynamic compression plate